Analysis of Makassar City Government's Readiness to Adopt Electric Vehicles Transportation Policy - Sumardi, Sumardi; Fatma, Fatma (Department of Government Studies, Universitas Muhammadiyah Buton., 2023)
The Indonesian government has taken significant strides towards promoting the adoption of electric vehicles (EVs) by offering subsidies to the public and encouraging local governments to embrace this sustainable transportation solution. This research aims to assess the preparedness of local governments, with a particular focus on Makassar City, in implementing policies to facilitate the integration of electric vehicles into their transportation systems. Employing a qualitative research approach, this study delves into statutory documents and regulations to gauge the progress and readiness of Makassar City's government in embracing EVs. The findings indicate that while the Makassar City Government has taken initial steps by introducing programs such as the Mobile Doctor Service Car program, Co'mo Car Electric Motor Program (Te'tere), and providing electric vehicles for officials, there is still a notable absence of comprehensive policies governing the use of electric vehicles. To ensure the sustained growth of EV adoption in Makassar City, it is imperative for the local government to formulate and enact relevant regulations, be it through regional laws, mayoral decrees, or other legal frameworks. These regulations should encompass various aspects of electric vehicle usage, including incentives, charging infrastructure, and sustainability practices. Additionally, the study underscores the importance of establishing a robust network of public electric vehicle charging stations to support the growing EV community in Makassar City. These facilities will play a pivotal role in enhancing the convenience and accessibility of electric vehicles for both residents and visitors, thus further promoting their adoption.